N-diklorofosforil-P-trikloromonofosfazenin değişik yöntemlerle alkillerinin sentezi - Arslan, Mustafa; Aslan, Fatih; Öztürk, İhsan; Görgülü, Orhan (My University, 2000)
-
31.01.2000
Keywords: Kimya; İnorganik ve Nükleer